EDUKASI CEGAH STUNTING SEBAGAI UPAYA PENCEGAHAN STUNTING PADA KELOMPOK IBU-IBU PKK - Mahihody, Astri; Alexander Tanod, Wendy; Rieuwpassa, Frets Jonas; Cahyono, Eko; Rorong, Miranda; Tampany, Ighen (Gapenas Publisher, 2024)
Stunting is a health problem that still receives serious attention from the government. Stunting has a negative impact on children's cognitive and physical development and can increase the risk of morbidity in adulthood. One of the community organizations that helps prevent stunting in the family environment is the Family Health Empowerment Group (PKK). According to the results of interviews with PKK administrators, education about stunting has been carried out in the Tahuna District. However, they still do not understand the explanation of stunting prevention. Therefore, stunting prevention education needs to be carried out in Tahuna Subdistrict, especially Soataloara 1, Mahena, and Santiago Villages. This community service activity aims to provide prevention education to prevent stunting in PKK women's groups in Tahuna District, Sangihe Islands Regency. The method of implementing this activity includes the stages of initial survey, preparation, and implementation. Before attending the stunting prevention counseling, the average value of knowledge of PKK mothers was only 68. However, after attending the counseling, the average value increased to 85. Stunting prevention education is presented in the form of PowerPoint presentations and videos. This is very effective in helping individuals understand difficult concepts and encourage them to learn more. This community service activity can increase the knowledge of PKK mothers about stunting prevention.